Assessment of a new solution for tracking pebbles in rivers based on active RFID. Issue 13 (5th June 2017) - Cassel, Mathieu; Dépret, Thomas; Piégay, Hervé
Abstract: Low‐frequency passive integrated transponders (PIT tags), are commonly used for monitoring pebble mobility in gravel‐bed rivers. Although early studies reported high recovery rates for PIT tags used in small streams, recovery rates in larger systems remain low, substantially limiting the possibilities for their use in such rivers. These low recovery rates are potentially due to missed detections caused by tag signal collision, burial in the sediment layer deeper than the maximum detection range and insufficient (but still exhausting) field effort to cover the concerned areas. A potential solution for addressing these problems is to use active ultra‐high frequency (a‐UHF) transponders as these have a greater detection range and anti‐collision protocols. In order to assess the potential of such transponders for pebble tracking in rivers, we used 433.92 MHz COIN‐ID and COIN‐HC models (ELA Innovation Company, Montpellier, France). We completed several tests to (i) characterize transponder detection ranges in the water and in saturated sediment and (ii) develop field protocols for locating tags by combining global positioning systems (GPS) sites and transponder received signal strength indication (RSSI) levels. The results showed that (i) the maximum detection ranges are about 2.4 m in the water column and more than 2.6 m in a column of saturated gravelly‐sandy sediment, (ii) RSSI spatial interpolation can be used to determine transponder position with good accuracy (< 1 m), (iii) the desired minimal level of accuracy can be adjusted depending on in‐field effort and signal impulse interval, (iv) the RSSI maximal value observed cannot yet be used to determine transponder burial depth because of the multipath propagation of radio frequencies and the semi‐directional emission of the tag signal. Copyright © 2017 John Wiley & Sons, Ltd.